In situ synthesis of mesoporous CdS nanoparticles in ternary cubic phase lyotropic liquid crystal - Huang, Nay Ming; Kan, C.S.; Radiman, S. (Springer, 2003)
An in situ technique for the synthesis of CdS nanoparticles in a ternary lyotropic cubic phase liquid crystal has been carried out. The extremely viscous cubic phase liquid-crystal system consists of poly(oxyethylene)10 nonly phenol ether as non-ionic surfactant, octane as oil phase and an aqueous phase containing reactant ions (Cd2+ and S2-). Thioacetamide (TAA) has been utilized as a source for slow release of sulfur in the in situ synthesis of CdS. Rheological results show that CdS nanoparticle growth did not disrupt the structure of the cubic phase liquid-crystal system. This indicates that homogenous synthesis of CdS in the liquid crystal had been achieved. The final products were characterized using X-ray photoelectron spectroscopy, thermal gravimetric analysis, transmission electron microscopy and UV-visible spectroscopy. It was found that the CdS nanoparticles formed have a mesoporous structure with a size dependent on the TAA decomposition aging time.